Effect of traditional birth attendants-led health education intervention on utilization of skilled birth care in West Pokot County, Kenya - Kaprom, Benadette C.; Ngure, Keneth; Mambo, Susan (International Journal Of Community Medicine And Public Health, 2024)
Background: Globally, between 2000 and 2017, maternal mortality ratio declined by 38%, with global lifetime risk of maternal death falling from 1 in 73 to 1 in 180, respectively. In West Pokot County, Kenya, over half of deliveries are managed by traditional birth attendants. The study investigated the effect of TBAs-led intervention on utilization of skilled birth care in this County. Methods: The study employed a prospective experimental design. In the intervention arm, TBAs were recruited and trained on SBC. They were assigned expectant mothers and followed until they delivered their babies. Chi-square test was used to determine the relationship between variables. Binary logistic regression was used to compare utilization of SBC between the intervention and control sites. Results: Majority of mothers (95%) in the intervention arm of the study went for TBAs’ services , and 79.5% of those in the control did the same. Most mothers in the intervention (81.4%) delivered in health care facility compared to 58.2% in the control (χ2=21.256, p<0.001). There was a significant difference in the odds of mothers utilizing SBC between intervention and control groups. Those in the intervention group were almost 3 times more likely to utilize SBC than those in the control group (UOR; 95% CI: 3.137; 1.909-5.155). Conclusions: TBAs-led intervention increased utilization of SBC among mothers in the intervention compared to those in the control arm who utilized available ministry of health’s standard care.